Analysis of E-Commerce Applications Using the System Usability Scale (SUS) Approach - Tri Wahyudi; Gunawan Budi Sulistyo; Nani Purwati; Noor Hasan (Universitas Teknokrat Indonesia, 2026)
This study aims to measure the level of satisfaction and effectiveness of the application, as well as the obstacles encountered, using the System Usability Scale (SUS) approach. The research employs a quantitative method with a questionnaire based on the System Usability Scale (SUS) to assess application usability. The population consists of Generation Z, with a sample of 411 respondents selected using cluster disproportionate random sampling. Data were analyzed to calculate the SUS score (0–100) and interpreted using the adjective scale. This study compares the usability of three e-commerce applications: Shopee, Tokopedia, and Lazada. The results indicate that the usability scores of the three e-commerce applications are relatively close: Shopee (90.06), Tokopedia (91.98), and Lazada (88.42). Based on gender, females prefer Shopee, while males favor Tokopedia and Lazada. In terms of age, the 20–24 age group is more dominant than the 15–19 age group. Meanwhile, based on occupation, students tend to use Lazada, whereas private employees prefer Shopee and Tokopedia. Shopee and Tokopedia demonstrate optimal performance, while Lazada has development potential, particularly for private employees and users aged 15–19. Further research is recommended to deepen the analysis of Lazada and include other regions and age groups for broader results.